Taxonomic revision of Leandra sect. Leandra (Melastomataceae, Miconieae) - Reginato, Marcelo (Phytotaxa, 2016)
A taxonomic monograph of a re-circumscribed Leandra sect. Leandra is presented. The new circumscription is based on a previous phylogenetic hypothesis, and diagnostic morphological characters are discussed. Four new combinations to Leandra are proposed, one from Clidemia (L. capilliflora) and three from Ossaea (L. capitata, L. cogniauxii and L. loligomorpha). Additionally, eight species are treated as synonyms for the first time, and 15 lectotypes are designated. A review of the 17 recognized species, including descriptions, synonymy, illustrations and distribution maps, is provided. This work also includes an overview of general morphology, leaf and flower anatomy, phenology and geographical distribution. Species with a history of taxonomic problems and/or with distinctive morphotypes are further investigated with morphometrics tools.